Quo Vadis: Legal Certainty and Justice in Indonesia's 2024 Elections Amidst Electoral Law Reform - Cahyani, Enny Dwi; Adawiyah Situmorang, Rabiatul; Sepulloh, Alif (LPPM Universitas Harapan Bangsa, 2025)
General Elections (Pemilu) are fundamental to Indonesia’s democratic system. However, their implementation continues to face challenges that hinder the realisation of a balanced relationship between substantive justice and legal certainty. This study offers a comprehensive examination of electoral issues, particularly emphasising the presidential threshold system, which has triggered multiple inequities in electoral practice. The objective of this research is to analyse the legal framework governing elections by critically assessing the validity of the presidential threshold, the complexities of the multi-party system, and the implementation of simultaneous elections, ultimately proposing a structured solution to the legal challenges of Indonesia's electoral system. The study adopts a normative juridical approach, complemented by a conceptual framework and comparative legal analysis, and is further supported by empirical data drawn from the 2019 and 2024 elections. The study employs legal interpretation and conceptual comparison methods, which indicate that the presidential threshold requires reformulation one that emphasises political inclusivity, leadership regeneration, and institutional refinement to ensure fairness and legal certainty in electoral governance.